A unique presentation of acute liver failure from herpes simplex virus hepatitis. Issue 4 (29th July 2016) - Gutierrez, C.; Kebriaei, P.; Turner, K.A.; Yemelyanova, A.; Ariza‐Heredia, E.J.; Foo, W.C.
Abstract: We present the case of a patient, with history of myelodysplastic syndrome and recent bone marrow transplant, who developed fulminant liver failure secondary to herpes simplex virus (HSV) hepatitis. His presentation was unique, as findings of liver microabscesses on computed tomography scan have not been described previously in this patient population. Despite initial treatment with acyclovir, he continued to deteriorate, and later sensitivities found the HSV strain to be resistant to acyclovir. HSV hepatitis with secondary liver failure is rare and, without appropriate treatment, its mortality is >80%. Early suspicion and immediate therapy are the keys to improve patient survival.